2018
DOI: 10.3389/fmicb.2018.01057
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Ketoglutarate in Low-Protein Diets for Growing Pigs: Effects on Cecal Microbial Communities and Parameters of Microbial Metabolism

Abstract: Alpha-ketoglutarate (AKG), a critical molecule in the tricarboxylic acid cycle, is beneficial to intestinal functions. However, its influence on intestinal microbiota and metabolism is not fully understood. We investigated the effects of a low-protein (LP) diet supplemented with AKG on cecal microbial communities and the parameters of microbial metabolism in growing pigs. Twenty-seven young pigs (Large White × Landrace) with an average initial body weight of 11.96 ± 0.18 kg were randomly allotted into three gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 76 publications
(101 reference statements)
3
26
2
Order By: Relevance
“…The decarboxylation and deamination of amino acids generate bioamines and ammonia, respectively. Ammonia, amines, phenols, and indoles are considered as potentially toxic products, which may interfere with epithelial cell turnover and inhibit pig growth (13, 24). In this study, S50 and CDCP had lower ammonia nitrogen and methylamine contents than P50 and FM (Table 3), possibly because plant protein (S50 and CDCP) contains dietary fiber, which help to reduce protein fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decarboxylation and deamination of amino acids generate bioamines and ammonia, respectively. Ammonia, amines, phenols, and indoles are considered as potentially toxic products, which may interfere with epithelial cell turnover and inhibit pig growth (13, 24). In this study, S50 and CDCP had lower ammonia nitrogen and methylamine contents than P50 and FM (Table 3), possibly because plant protein (S50 and CDCP) contains dietary fiber, which help to reduce protein fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…The contents of ammonia nitrogen (NH 3 -N) in samples were determined using Nessler's reagent spectrophotometry as described by Chen et al (24). Briefly, 0.5 g of colonic digesta was mixed with 5 mL of ammonia-free water and centrifuged at 5,000 × g for 15 min at 4°C to collect the supernatants.…”
Section: Methodsmentioning
confidence: 99%
“…TCA are metabolic intermediates of Krebs cycle, thus involved in energy metabolism. These acids improve gut morphology and barrier function, with a favorable influence on microbiota [11,12].…”
Section: Classification Of Organic Acidsmentioning
confidence: 99%
“…All pigs were weighed individually at the beginning and the end of the experiment. The feed consumption was recorded at the end of the experiment to calculate average daily gain, average daily feed intake, and feed-to-gain ratio, as previously described [15]. When the feeding experiment ended, 8 mL blood samples were collected via jugular vein puncture into 10 mL tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Yao et al (2013) reported that mTOR pathway was induced by AKG supplementation, which increased skeletal muscle mass in rats [14]. Our previous study demonstrated that the addition of AKG to a low-protein diet improved growth performance [15] and promoted the cells in skeletal muscles to synthesize amino acids in growing pigs [16]. Additionally, the muscular fiber and fatty acid composition in pig skeletal muscles were modulated by the dietary supplementation of monosodium l -glutamate [3].…”
Section: Introductionmentioning
confidence: 99%